The art of modeling stellar mergers and the case of the B[e] supergiant R4 in the Small Magellanic Cloud - Wu, Samantha; Schneider, Fabian (The astrophysical journal, 2020)
Most massive stars exchange mass with a companion, leading to evolution which is altered drastically from that expected of stars in isolation. Such systems result from unusual binary evolution pathways and can place stringent constraints on the physics of these interactions. We use the R4 binary system’s B[e] supergiant, which has been postulated to be the product of a stellar merger, to guide our understanding of such outcomes by comparing observations of R4 to the results of simulating a merger with the 3D hydrodynamics code FLASH. Our approach tailors the simulation initial conditions to observed properties of R4 and implements realistic stellar profiles from the 1D stellar evolution code MESA onto the 3D grid, resolving the merger inspiral to within 0.02 R ⊙. We map the merger remnant into MESA to track its evolution on the H-R diagram over a period of 104 yr. This generates a model for a B[e] supergiant with stellar properties, age, and nebula structure in qualitative agreement with those of the R4 system. Our calculations provide evidence to support the idea that R4's B[e] supergiant was originally a member of a triple system in which the inner binary merged after its most massive member evolved off the main sequence, producing a new object of similar mass but significantly more luminosity than the A supergiant companion. The code framework presented in this paper, which was constructed to model tidal encounters, can be used to generate accurate models of a wide variety of merger stellar remnants.
Gesehen am 26.10.2021